1996
DOI: 10.1038/nm0396-287
|View full text |Cite
|
Sign up to set email alerts
|

Impaired wound healing in mice with a disrupted plasminogen gene

Abstract: Activation of plasminogen (Plg) has been proposed to play a role in proteolytic degradation of extracellular matrices in tissue remodeling events, including wound healing. However, there has been no definitive proof of involvement of Plg in such processes. We now report that healing of skin wounds is severely impaired in mice made deficient in Plg by targeted gene disruption. The results demonstrate that Plg is required for normal repair of skin wounds in mice and support the assumption that it also plays a ce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

19
375
1
6

Year Published

1997
1997
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 543 publications
(403 citation statements)
references
References 35 publications
19
375
1
6
Order By: Relevance
“…Confirming the absolute requirement of plasminogen for cell migration, neovascularization, and wound healing, 26,27 we found that both Ad-control and Ad-TFPI2-infected cells failed to migrate in the absence of plasminogen even after 48 hours. No significant difference was observed between the healing index values among the time points or the conditions tested (Figure 5f through 5h).…”
Section: Tfpi-2 Inhibits Ec Migration In Vitrosupporting
confidence: 73%
“…Confirming the absolute requirement of plasminogen for cell migration, neovascularization, and wound healing, 26,27 we found that both Ad-control and Ad-TFPI2-infected cells failed to migrate in the absence of plasminogen even after 48 hours. No significant difference was observed between the healing index values among the time points or the conditions tested (Figure 5f through 5h).…”
Section: Tfpi-2 Inhibits Ec Migration In Vitrosupporting
confidence: 73%
“…However, injection of mBSA into knee joints creates a trauma. Persistent deposition of fibrin has been observed in traumas in plasminogen-deficient mice (18). In this respect, fibrin deposition in plasminogen-deficient mice in AIA may be a consequence of the inflammation associated with trauma rather than being the reason for the inflammation of arthritis, or both.…”
Section: Discussionmentioning
confidence: 97%
“…The main function of the PA system is fibrinolysis, which is important for the maintenance of the hemostatic balance (16). However, by acting in concert with other proteinases, the PA system has also been proposed to play a role in the remodeling and degradation of the ECM during many physiologic and pathologic processes, including ovulation (17), skin wound healing (18), tumor invasion (19,20), and inflammatory cell infiltration, fibrin deposition, and joint destruction associated with RA (21). However, despite the rapid progress in our understanding of the involvement of the PA system in RA, the molecular mechanisms by which the PA system participates in the pathogenesis of RA are still poorly understood.…”
mentioning
confidence: 99%
“…Plg deficiency has been associated with defective removal of necrotic debris in experimental models of liver fibrosis and epithelial wound healing. 18,19,23,45,54 Although plasmin has a broad substrate specificity in vitro, its targeted substrates in vivo are not well defined. Fibrin deposition has been proposed as a critical feature in the pathologies associated with plg deficiency.…”
Section: Discussionmentioning
confidence: 99%